Pengaruh Model Pembelajaran Kooperatif dan Gaya Berpikir terhadap Hasil Belajar - Khambali (Al-Ma‘rifah, 2018)
The objective of this research was to investigate comprehensively the effect of learning model and student's thinking style on the Arabic reading achievement of the second semester student of the Islamic Studies Program, the Institut of Islamic Studies of Indonesia Jakarta, academic year 2016/2017. This was an experimental research using a two-factor ANOVA at 0,05 and 0,01 significance level. The data was collected using the Arabic reading test and thinking style questionaire. The findings above led to a conclusion that the result of arabic reading in cooperatif of MM was higher than cooperatif of NHT, Students who has divergen thinking style was higher than student who has covergent thinking, and its happened an interaction between cooperatif model teaching and thinking style to the result of arabic reading.